CAR-T Cell Therapy in Gastrointestinal Cancer, Head and Neck Cancer, and Autoimmune Diseases: Current Advances and Future Perspectives - Kania, Martyna; Bartkowiak , Hanna; Grubski, Damian; Adamowska, Agnieszka; Nadolny, Filip; Janecka, Julia; Jabłoński, Jędrzej; Śniatała, Alicja; Hofman, Michał; Dudek, Adam (Journal of Education, Health and Sport, 2025)
Introduction: Chimeric Antigen Receptor (CAR) T cell therapy has revolutionized cancer treatment, showing significant success in hematologic malignancies. However, its application in solid tumors like gastrointestinal (GI) and head and neck cancers, as well as autoimmune diseases, remains a challenge. The development of CAR-T cell therapy for these indications presents unique difficulties, including tumor heterogeneity, antigen specificity, and immune suppression within the tumor microenvironment. Aim of the study: This review aims to provide an in-depth analysis of the current advancements in CAR-T cell therapy for gastrointestinal cancer, head and neck cancer, and autoimmune diseases. We seek to evaluate the therapeutic potential, current challenges, and future directions of CAR-T cell-based interventions in these conditions. Materials and methods: We performed a comprehensive literature review, analyzing recent clinical trials, preclinical studies, and research published in PubMed and Google Scholar. We focused on CAR-T cell therapy targeting solid tumors and autoimmune diseases, current treatment options, clinical efficacy, and safety concerns across these therapeutic areas. Conclusions: CAR-T cell therapy has shown promising potential in the treatment of gastrointestinal cancers, head and neck cancers, and autoimmune diseases, but its clinical application remains limited by challenges such as antigen escape, off-tumor toxicity, and insufficient T-cell persistence. Future studies must focus on improving CAR design, enhancing targeting accuracy, and addressing the immunosuppressive tumor environment to unlock the full therapeutic potential of CAR-T cells for these indications.